Effect of audio distraction with thermomechanical stimulation on pain perception for inferior alveolar nerve block in children: a randomized clinical trial - Nagpal, Devendra; Amlani, Dharanshi Viral; Rathi, Pooja; Hotwani, Kavita; Singh, Prabhat; Lamba, Gagandeep (Journal of Dental Anesthesia and Pain Medicine, 2023)
Pain control is a crucial aspect of pediatric dentistry for patient management. Thermo-mechanical devices (Buzzy™ Pain Care Labs, USA) work on the concept of vibration and cooling and have shown promising results in pain control during local anesthesia in pediatric dentistry. On the other hand, audio distraction has also been used for pain management. The amount of pain endured is determined by the patient's perception and attentiveness. Thus, if audio function is added to the thermomechanical device it might increase its efficiency. Hence, the present study aimed to compare pain on injection using a thermo-mechanical device with and without audio during inferior alveolar nerve block (IANB) injection in children aged 5-10 years old. Twenty-eight children aged between 5 and 10 indicated for IANB were included in this randomized study. Children who were undergoing the dental procedure were divided into 2 groups, with 14 children in each group. The study group was the thermo-mechanical device with audio distraction; the control group was the thermo-mechanical device without audio distraction. IANB was administered. Subjective pain evaluation was performed using the Wong-Baker Faces Pain Rating Scale (WBFPR) and objective pain evaluation was done using the Faces, Leg, Activity, Consolability, Cry (FLACC) scale. The outcome depicted a significant reduction in pain on injection for both objective and subjective evaluations in the thermo-mechanical device with an audio distraction group. Less pain on injection was observed, when a thermo-mechanical device was used with audio distraction for IANB procedures.